Comparative Study Regarding The Gum-Periodontal Manifestations During Pregnancy And Non-Pregnancy - Liliana Sachelarie; Adina Simona Birgaoanu; Carmen Stadoleanu; Diana Popovici; Florentina Pricop (Romanian Society of Oral Rehabilitation, 2011)
The pregnancy, by itself is not able to produce the taint of the limit paradont but the hormonal change together with the vitamin deficit which occures during this periode may affect the local reaction of tissues concerning the bacterial plack, the real cause of this problem. In case of pregnancy woman the bacterial flora inside protection against it decreases, so the oral hygiena and the alimentation hold the main role in the evolution of the gingivo - paradontal diseases. A comparative study involving 25 pregnancy woman and 25 unpregnant over shows that the appearance of gingivo -parodontal diseases is bigger in the first lot that the second one. We also concluded that, in case of pluri -even pregnant woman, the paradontal teritory is more affected because of the previous pregnancies.